O PROJETO ÉTICO-POLÍTICO DO KUYPERIANISMO: APONTAMENTOS HISTÓRICOS, TEOLÓGICOS E SEU PROCESSO DE RECEPÇÃO NO BRASIL CONTEMPORÂNEO - Almeida, Vinnícius Pereira de (2019)
This study investigates the life and work of Abraham Kuyper, the Dutch theologian and statesman. His biography and proposals for education, social matters, the church, and the political scene form the two axes which are studied as constituting the origin of neocalvinism as a movement that legitimates the comprehension of divine sovereignty over all spheres of life attached to a position of commitment to the public arena. As demonstrated in the first chapter, Kuyper lead the edition of a newspaper and a political party, established the Free University of Amsterdam, participated in a movement to found the Free Reformed Church and gave the Stone Lectures. Then the development of Kuyper’s perspective and theological thought is presented in the second chapter as the foundation sustaining the recognition of an ethic-political project. Following, in the third chapter, through bibliographical research, it is presented the process of translation and publication of works in reformed philosophy and institutions that foster and promote the neocalvinist thought in Brazil. In the concluding considerations, it is explicitly demonstrated the elements that this study could assess and the analytical contributions are highlighted: the challenge of contextualizing a Dutch theology from the 19th century in 21st century Brazil; and the possibilities of making a contribution by attaching new theoretical and methodological elements, and action strategies of articulating the Christian faith before sociopolitical confrontations